Growth response of holm oak (Quercus ilex L) to commercial thinning in the Montseny mountains (NE Spain) (Ann. For. Sci., 1993)
Growth responses of holm oak (Quercus ilex) to commercial thinning were studied in the Montseny Biosphere Reserve (northeast Spain), where selection thinning for firewood production is currently the dominant form of management in holm oak forests. Thinning significantly increased mean stem diameter increment by 83% over that of unthinned plots during the 6-9-yr period after thinning, and by 48% from 9-12 yr after thinning. Absolute diameter increment was positively correlated with initial diameter at 1.30 m from the ground (dbh) both in thinned and unthinned plots. Thinning increased growth in large trees more than in smaller trees. Relative diameter growth was negatively correlated with initial dbh. It is concluded that individual holm oak stems in previously coppiced stands respond vigourously to thinning, and still do so 6-9 yr after thinning. The growth response diminishes 9-12 yr after thinning due to canopy closure. However, absolute rates of stand growth, as well as basal area and stem biomass increments, were unaffected by thinning during these time intervals, an example of density compensation.